Condolences to Turkmen in the city of Erbil: Anthropological Study - Rashad Sabre Meran; Nadia Wali Jabbar (QALAAI ZANIST JOURNAL, 2022)
Erbil, where I observed the condolences of the Turkmen and participated in it; The researcher lives in the city of Erbil and has relations and interactions with the Turkmens living in Erbil. The main question of this research is: Condolences for the Turkmen in the city of Erbil - how are things going? Or how is his procedure? What is the difference between solace in the present and the past? What is the difference between the mourning of men and the mourning of women? What is the meaning of condolences and what is its social function? How is this ceremony carried out in the era of the Corona epidemic? The aim of this research is to shed light on the concepts, meanings, and procedures that are observed and implemented in mourning for the Turkmen in the city of Erbil, as well as discussing the way in which mourning for men and women is performed and to reveal some of the main issues in the Turkmen culture during their mourning. Then, he explained the effects of the spread of the Corona epidemic on the concept and meaning of condolences for the Turkmen in the city of Erbil. The researcher used the ethnographic method in her research, which includes data collection tools such as individual interviews, notes, and participatory observation. Among the main results of this research: The change in the way of administering condolences and its procedures among the Turkmen significantly between the past and the present, due to the presence of changes in their lifestyle and the spread of the Corona epidemic, and the purpose and presentation behind the establishment of condolences for them have also changed. The presence of changes in the period of mourning and mourning Sadlian, and a reduction in the number of visits to cemeteries and crying and mourning in the forties...etc. The funeral procession of Turkmen men and women differs in how it is conducted. Those meanings and signs that are observed in the funerals of women are not found in the funerals of men.